Laparoscopic surgery for atypical endometrial hyperplasia with awareness regarding the possibility of endometrial cancer - Misato Kamii; Yoko Nagayoshi; Kazu Ueda; Motoaki Saito; Hirokuni Takano; Aikou Okamoto (Wolters Kluwer Medknow Publications, 2023)
Objectives: Although atypical endometrial hyperplasia (AEH) is considered a precancerous disease, the frequency with which AEH and endometrial cancer (EC) coexist is not low. Broadly, total laparoscopic hysterectomy (TLH) is performed for treating AEH; however, it is unclear what perioperative precautions need to be taken. This study aimed to clarify the points to be considered when performing TLH for AEH. Materials and Methods: We retrospectively identified 57 patients who underwent TLH for AEH in our hospitals. We extracted data on clinical characteristics, preoperative examinations (endometrial sampling and diagnostic imaging), surgical procedures, and final pathological diagnoses. Then, we statistically analyzed the difference in clinicopathological features and preoperative examinations between patients postoperatively diagnosed with EC and those diagnosed with AEH. Results: Twenty patients (35%) who underwent TLH for AEH were diagnosed with EC postoperatively (16 [28%] with stage IA EC and four [7.0%] with stage IB EC). We found no significant differences in clinical characteristics and preoperative evaluations between patients postoperatively diagnosed with EC and those diagnosed with AEH. The group with stage IB EC had a significantly higher median age and a significantly higher proportion of postmenopausal patients and patients with adenomyosis. Conclusion: It is important to recognize the risk of coexisting EC when performing TLH for AEH. High-precision endometrial sampling and contrast-enhanced magnetic resonance imaging are recommended for diagnosing AEH. In addition, surgical procedures for AEH are required to prevent cancer spillage in consideration of its coexistence, such as tubal sealing before manipulator insertion or avoiding using manipulator.